Detection quality of ultralow magnetic susceptibility and residual magnetic moment, preparation method and application
Through vacuum electron beam smelting and induction smelting combined with multi-directional forging and surface treatment, the problem that the susceptibility and residual magnetic moment of Au-Pt alloy are difficult to meet the gravitational wave detection requirements, and the efficient preparation of ultra-low magnetic moments and residual magnetic moments is achieved. The detection quality meets the technical indicators of gravitational wave detection.
Patent Information
- Application Number
- CN202411323183.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing Au-Pt alloys are used in the inspection quality of gravitational wave detection. The magnetic susceptibility and residual magnetic moment are difficult to meet the technical requirements of gravitational wave detection, and the magnetic noise generated by the material in the space magnetic field is difficult to control.
Au-Pt alloy is prepared by vacuum electron beam smelting and induction smelting. Through multiple smelting and annealing, combined with multi-directional forging and surface treatment, it avoids contact with ferromagnetic elements, significantly reduces the content of impurity elements and improves purity.
It significantly reduces the magnetic susceptibility and residual magnetic moment of Au-Pt alloy, improves production efficiency, meets the technical index requirements of gravitational wave detection, and provides ultra-low magnetic susceptibility and residual magnetic moment detection quality.
Smart Images

Figure BDA0005054594150000061 
Figure HDA0005054594160000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of precious metal processing, and in particular to the detection quality, preparation method and application of ultra-low magnetic susceptibility and residual magnetic moment. Background Art
[0002] Gravitational wave detection is recognized by the world scientific community as one of the most difficult cutting-edge technologies. Its basic principle is to use a laser interferometer ranging system to accurately measure the distance changes between the test masses inside the satellite at the picometer level to detect the space-time distortion caused by gravitational waves. Therefore, it can be said that the test mass is a key component in the gravitational wave detection system. When the spacecraft is in operation, the test mass is in the constantly changing space magnetic field and the magnetic field generated by the spacecraft itself. The magnetic noise to the test mass is one of the main sources of residual acceleration noise, and its size depends on the magnetic field in which it is located and the magnetic susceptibility and remanent magnetic moment of the test mass. Since the space magnetic field is uncontrollable and low-frequency signals cannot be completely shielded, the key to reducing magnetic noise is to develop a test mass with ultra-low magnetic susceptibility and remanent magnetic moment. At the same time, the material of the test mass used for space gravitational wave detection must also meet the requirements of high density and hardness, stable chemical properties, good thermal conductivity and electrical conductivity. At present, mixing diamagnetic Au and paramagnetic Pt in a certain proportion to form an Au-Pt alloy with near-zero magnetic susceptibility is the most promising technical solution for test mass preparation, but the values of its magnetic susceptibility and remanent magnetic moment are still difficult to meet the requirements of gravitational wave detection applications. Summary of the invention
[0003] In view of the above problems, the present invention provides a method for preparing a test mass with ultra-low magnetic susceptibility and remanent magnetic moment. While improving production efficiency, the preparation method greatly reduces the content of ferromagnetic impurity elements in the test mass, has higher purity, and significantly reduces the remanent magnetic moment of the Au-Pt alloy test mass, thus meeting the technical index requirements for gravitational wave detection.
[0004] In order to achieve the above object, the present invention provides a method for preparing a detection mass with ultra-low magnetic susceptibility and remanent magnetic moment, comprising the following steps:
[0005] Melting: weigh the raw materials, melt them by vacuum electron beam melting method, melt them, keep them warm, pour them, form ingots, cool them, solidify them, and melt them;
[0006] Preparation and inspection quality: anneal the ingot after melting and casting, cut it into pieces to obtain several ingot blocks, multi-directionally forge the ingot blocks, and perform surface treatment to obtain inspection quality.
[0007] In the above preparation method, high vacuum electron beam melting is first used for melting, and the saturated vapor pressure of each element is used to purify gold and platinum. The purified raw materials are then melted into alloy ingots using a conventional induction melting method, which can further reduce the content of impurity elements compared to direct melting.
[0008] In one embodiment, there are cleaning and drying steps before the step of weighing the raw materials.
[0009] In one embodiment, the cleaning is ultrasonic cleaning, and the ultrasonic cleaning and drying include: immersing and cleaning with acetone for 2 to 3 times to remove surface oil stains, pickling with hydrochloric acid solution for 3 to 4 times to remove surface impurities, using anhydrous ethanol to place in a 3200H ultrasonic cleaner for 10 to 15 minutes to wash away the hydrochloric acid solution remaining on the surface of the raw material, repeatedly rinsing with deionized water, and placing in an oven at 120°C for 3 hours.
[0010] In one embodiment, in the ultrasonic cleaning and drying steps, the hydrochloric acid solution contains 36.00-38.00% HCl.
[0011] In one embodiment, the raw materials include Au and Pt, and the mass of the raw materials is ≥ 3-4 kg × the number of detected masses.
[0012] The preparation method adopts large-mass ingot casting, which can cast several inspection-quality ingots that meet the quality requirements at one time, and significantly improves the production efficiency compared with other preparation methods.
[0013] In one of the embodiments, the content of Au in the detection mass is 60-80% by mass.
[0014] In one of the embodiments, in the step of weighing the raw materials, the weighed amount of Au is 0.05%-0.15% higher than the content of Au in the detected mass.
[0015] In one embodiment, the purity of the raw material is 99.99%.
[0016] In one embodiment, the smelting temperature is 150-250° C. higher than the melting point of the raw material, and the smelting time is 3-5 min; the heat preservation is achieved by a graphite crucible.
[0017] In one embodiment, the insulation time is 3-5 minutes.
[0018] In one embodiment, the pouring includes: pouring the heat-insulated melt into a water-cooled copper mold; the number of times of the casting is 3-5 times.
[0019] In one embodiment, the water-cooled copper mold is cylindrical, with a diameter-to-height ratio of 2:1 to 4:1; the pouring speed is controlled during pouring so that the molten metal is uninterrupted and the ingot is gradually solidified. When the ingot is melted again, the ingot is turned around and then placed in the melting furnace for remelting.
[0020] In one embodiment, the cutting is achieved by a lathe, and the raw material of the tool head of the lathe is diamond.
[0021] In one of the embodiments, the annealing temperature is 900-1250° C., and during the annealing process, the ingot is placed in a high-temperature material container.
[0022] In one embodiment, the high temperature material does not contain magnetic material.
[0023] In one embodiment, the high temperature material includes tungsten and graphite; a titanium alloy clamp that does not contain magnetic materials is used to clamp the ingot.
[0024] In one embodiment, the multi-directional forging is achieved by an air hammer, the hammer head of the air hammer is coated with a copper sheet, the multi-directional forging is performed for 8-20 passes, the forging temperature of the multi-directional forging is 800-1200°C, and the single forging deformation of the multi-directional forging is ≤5%.
[0025] In one of the embodiments, before the multi-directional forging step, the hammer head and the workbench of the air hammer are wiped with alcohol; the thickness of the copper sheet is 0.1mm-2mm.
[0026] The alcohol wiping can ensure a clean working environment and avoid the introduction of impurities; the copper sheet can prevent the upper and lower hammers from directly contacting the ingot block.
[0027] In one embodiment, the size of the ingot block after multi-directional forging is a cube with a side length of ≥50 mm.
[0028] In one of the embodiments, the surface treatment is achieved by a milling machine, and the raw material of the cutter head of the milling machine is a cemented carbide that does not contain magnetic materials.
[0029] The inventors found in the study that the most important factor affecting the magnetic susceptibility of Au-Pt alloy is the content of Pt element, while the main factor affecting the remanent magnetic moment of Au-Pt alloy is the content of ferromagnetic impurity elements in the test mass. Therefore, in the whole process of processing Au-Pt alloy test mass, in order to reduce the content of ferromagnetic impurity elements in the test mass, it is necessary to avoid direct contact between the Au-Pt alloy test mass and equipment, molds, cutters, tools, etc. containing ferromagnetic elements such as Fe, Co, and Ni as much as possible, so as to reduce the content of ferromagnetic impurity elements in the test mass to the greatest extent, thereby reducing the magnetic susceptibility and remanent magnetic moment of the test mass, so that it meets the technical index requirements of gravitational wave detection.
[0030] In one of the embodiments, the surface treatment includes: processing the ingot block after multi-directional forging to make the surface flat and smooth, without cracks, inclusions, and pores, and the surface roughness is ≤0.2μm.
[0031] In one embodiment, the size of the single proof mass after surface treatment is (50±1) mm×(50±1) mm×(50±1) mm.
[0032] The present invention also provides a detection mass obtained by the preparation method, wherein the magnetic susceptibility of the detection mass |χ|≤8*10 -6 , residual magnetic moment ≤25nAm 2 .
[0033] The present invention also provides application of the detection mass in a gravitational wave detection system.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The ultra-low magnetic susceptibility and residual magnetic moment detection mass and its preparation method and application of the present invention, the Au-Pt alloy inspection mass for gravitational wave detection obtained by the preparation method, in the whole processing process, by melting a large mass ingot, multiple inspection masses can be processed at one time, which can effectively improve the production efficiency. And different from the gravitational wave detection alloy materials obtained by previous research, the gravitational wave detection alloy materials are mainly formed into rod-shaped raw materials by regulating the alloy composition, dense and uniform heat treatment and other measures, rather than inspection masses that can be directly launched into space for application. In this case, the contact between the Au-Pt alloy block and the heat treatment furnace is isolated by a customized high-temperature material box during heat treatment, the contact between the Au-Pt alloy block and the upper and lower hammer heads of the air hammer is isolated by a Cu sheet during forging, and the contact between the Au-Pt alloy block and the tools and accessories containing ferromagnetic elements is processed by diamond and carbide tool heads during milling, etc., so as to avoid the contact between the Au-Pt alloy and the tools and accessories containing ferromagnetic elements in all directions, and prepare the inspection mass, and the verification experiment confirms that the inspection mass prepared by the present invention has ultra-low magnetic susceptibility and residual magnetic moment, and the magnetic susceptibility is less than 6.5×10 -6 , remanent magnetic moment<18nAm 2 This preparation method not only improves production efficiency, but also greatly reduces the content of ferromagnetic impurity elements in the test mass, has higher purity, and significantly reduces the magnetic susceptibility and remanent magnetic moment of the Au-Pt alloy test mass, meeting the technical index requirements for gravitational wave detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the inspection quality of the qualified Au-Pt alloy obtained by the preparation method of Example 1. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] definition:
[0040] Detection mass: In the present invention, the detection mass is the core sensor in the gravitational wave detection system, and its shape is a cube.
[0041] source:
[0042] Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0043] Example 1
[0044] A detection mass and preparation method for ultra-low magnetic susceptibility and remanent magnetic moment.
[0045] The preparation method is specifically as follows:
[0046] The Au and Pt raw materials with a purity of ≥99.99% were soaked and cleaned with acetone for 2 to 3 times to remove surface oil stains, and then pickled with concentrated hydrochloric acid solution (containing HCl 36.00-38.00%) for 3 times to remove surface impurities. Then, anhydrous ethanol was placed in a 3200H ultrasonic cleaner for cleaning for 10 minutes to wash away the hydrochloric acid solution remaining on the surface of the raw materials. After that, it was repeatedly rinsed with deionized water and placed in an oven for drying at 120°C for 3 hours. After ultrasonic cleaning and drying, the clean and dry Au and Pt raw materials were weighed according to the Au-26Pt alloy using an electronic balance (the mass percentage of Au in the final detection mass is 60-80%, and the mass percentage of Pt is 20-40%). In the process of weighing the raw materials, 0.05wt.% to 0.15wt.% of Au raw materials were weighed more than the content of Au in the detection mass (the total mass of Au raw materials is 8g), and the total mass of the raw materials was 10.86kg. The alloy is melted in a vacuum electron beam melting furnace. A high-purity graphite crucible is used to keep the Au and Pt raw materials warm for 5 minutes after they are completely melted. The melt is then poured into a cylindrical water-cooled copper mold. After the ingot cools and solidifies, it is melted again and refined repeatedly for 3 times. During the melting process, the melting temperature is 200°C higher than the melting point, and the melting time is 5 minutes each time. The diameter and height ratio of the cylindrical water-cooled copper mold used is 5:1. The pouring speed is controlled during pouring to ensure that the melt is uninterrupted and the ingot gradually solidifies. When melting and casting again, the ingot is turned around and placed in the melting furnace for remelting.
[0047] The repeatedly refined ingots were homogenized and annealed at 1000°C using a box-type resistance furnace. During annealing, the Au-Pt test mass was placed in a customized high-temperature material cubic box (such as a tungsten box, a graphite box, etc.), and the Au-Pt alloy test mass was clamped using a customized titanium alloy fixture that does not contain ferromagnetic elements such as Fe, Co, and Ni. The ingot was divided into three sections using a lathe, and the masses of the three sections were 3.28kg, 3.52kg, and 3.61kg, respectively.
[0048] Each ingot was subjected to 12 multi-directional forgings by air hammer, and the forging temperature was 800℃. The size of the forged Au-Pt alloy inspection mass was a cube with a side length of (54±1) mm. Before multi-directional forging of the ingot, the hammer head and workbench of the air hammer were wiped with alcohol to ensure a clean working environment and avoid the introduction of impurities. During forging, the upper and lower hammer heads of the air hammer were covered with a Cu sheet with a thickness of 1 mm to avoid direct contact between the upper and lower hammer heads and the inspection mass ingot, and the deformation of a single forging was controlled to be 5%. The surface of each Au-Pt alloy inspection mass was processed flat and smooth by a milling machine, and the milling machine head was selected from cemented carbide without ferromagnetic elements such as Fe, Co, and Ni. The sizes of the three Au-Pt alloy inspection masses formed in the end were 50.5mm×51.0mm×50.6mm, 50.6mm×50.4mm×50.3mm, and 50.2mm×50.5mm×50.5mm, respectively. After the surface of the gold-platinum alloy is processed by a milling machine to inspect its quality, the surface is required to be free of defects such as cracks, inclusions, pores, etc., and the surface roughness is 0.2μm.
[0049] Comparative Example 1
[0050] The Au and Pt raw materials with a purity of ≥99.99% were soaked and cleaned with acetone for 2 to 3 times to remove surface oil stains, and then pickled with concentrated hydrochloric acid solution (containing HCl 36.00-38.00%) for 3 times to remove surface impurities. Then, anhydrous ethanol was placed in a 3200H ultrasonic cleaner for cleaning for 10 minutes to wash away the hydrochloric acid solution remaining on the surface of the raw materials. After that, it was repeatedly rinsed with deionized water and placed in an oven for drying at 120°C for 3 hours. After ultrasonic cleaning and drying, the clean and dry Au and Pt raw materials were weighed according to the Au-26Pt alloy using an electronic balance (the mass percentage of Au in the final detection mass is 60-80%, and the mass percentage of Pt is 20-40%). In the process of weighing the raw materials, 0.05wt.% to 0.15wt.% of Au raw materials were weighed more than the content of Au in the detection mass (the total mass of Au raw materials is 2.6g), and the total mass of the raw materials was 3.54kg. The alloy is melted in a vacuum electron beam melting furnace. A graphite crucible is used to keep the Au and Pt raw materials warm for 5 minutes after they are completely melted. The melt is then poured into a cylindrical water-cooled copper mold. After the ingot cools and solidifies, it is melted again and refined repeatedly for 3 times. During the melting process, the melting temperature is 200°C higher than the melting point, and the melting time is 5 minutes each time. The diameter and height ratio of the cylindrical water-cooled copper mold used is 3:1. The pouring speed is controlled during pouring to ensure that the melt is uninterrupted and the ingot gradually solidifies. When melting and casting again, the ingot is turned around and placed in the melting furnace for remelting.
[0051] The repeatedly refined ingot was homogenized and annealed at 1000°C in a box-type resistance furnace.
[0052] The ingot was multi-directionally forged 12 times with an air hammer at a forging temperature of 800°C. The size of the forged gold-platinum alloy test mass was a cube with a side length of (54±1) mm. The surface of the gold-platinum alloy test mass was processed flat and smooth using a milling machine. The dimensions of the final Au-Pt alloy test mass were 50.2mm×50.5mm×50.4mm. After the surface of the gold-platinum alloy test mass was processed by a milling machine, it was required to be free of defects such as cracks, inclusions, pores, etc., and the surface roughness was 0.2μm.
[0053] Experimental example
[0054] 1. Test the detection quality prepared by the above method.
[0055] Test method: GB / T15072.1-2008, GB / T15072.3-2008, GB / T25934.2-2010, YS / T1493-2021, YS / T372.2-2006
[0056] The magnetic susceptibility and remanent magnetic moment measurement method is: use the PPMSDynaCool type comprehensive physical property measurement system (PPMS) to test the volume magnetic susceptibility of Au-Pt alloy. The comprehensive physical property measurement system is a fully automatic platform for comprehensive measurement of various physical properties (covering various measurement functions such as magnetism, electricity, and heat). On the one hand, it provides a wide range of temperature research ranges, magnetic field research ranges, common electronic circuits, and various measurement common control interfaces. On the other hand, it can also provide a variety of physical properties based on this platform. Automatic measurement methods and corresponding measurement devices. The surface of the Au-Pt alloy sample was manually polished and cut into strip samples with a size of 4mm×6mm and a mass greater than 0.5g. It was cleaned with hydrochloric acid for 2 to 3 times, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes. After drying, the magnetic susceptibility and remanent magnetic moment were tested.
[0057] 2. After testing, the impurity components of the three Au-Pt alloy test masses (test masses 1, 2, and 3) obtained by the preparation method of Example 1 are shown in the following table. The magnetic susceptibility and remanent magnetic moment are (5.8±0.5)×10 -6 and (17.4±0.2)nAm 2 The impurity components of the Au-Pt alloy prepared in the comparative example are shown in the following table. The magnetic susceptibility and remanent magnetic moment are 10.3×10 -6 and 35.7nAm 2 The quality of the qualified Au-Pt alloy obtained by the preparation method of Example 1 is as follows: Figure 1 shown.
[0058] Table 1 Impurity components of each test mass
[0059]
[0060]
[0061] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a detection mass with ultra-low magnetic susceptibility and remanent magnetic moment, characterized in that: The following steps are involved: Melting: weigh the raw materials, melt them by vacuum electron beam melting method, melt them, keep them warm, pour them, form ingots, cool them, solidify them, and melt them; Preparation and inspection quality: anneal the ingot after melting and casting, cut it into pieces to obtain several ingot blocks, multi-directionally forge the ingot blocks, and perform surface treatment to obtain inspection quality.
2. The preparation method according to claim 1, characterized in that: The raw materials include Au and Pt, and the mass of the raw materials is ≥3-4 kg×the number of detected masses.
3. The preparation method according to claim 1, characterized in that: The smelting temperature is 150-250° C. higher than the melting point of the raw material, and the smelting time is 3-5 minutes; the heat preservation is achieved by using a graphite crucible.
4. The preparation method according to claim 1, characterized in that: The cutting is achieved by a lathe, and the raw material of the tool head of the lathe is diamond.
5. The preparation method according to claim 1, characterized in that: The annealing temperature is 900-1250° C. During the annealing process, the ingot is placed in a high-temperature material container.
6. The preparation method according to claim 5, characterized in that: The high temperature material does not contain magnetic material.
7. The preparation method according to claim 1, characterized in that: The multi-directional forging is achieved by an air hammer, the hammer head of the air hammer is covered with a copper sheet, the multi-directional forging is performed for 8-20 passes, the forging temperature of the multi-directional forging is 800-1200° C., and the single forging deformation of the multi-directional forging is ≤5%.
8. The preparation method according to claim 1, characterized in that: The surface treatment is achieved by a milling machine, and the raw material of the cutter head of the milling machine is a hard alloy that does not contain magnetic materials.
9. The detection mass obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The magnetic susceptibility of the detection mass |χ|≤8*10 -6 , residual magnetic moment ≤25nAm 2 .
10. Application of the detection mass described in claim 9 in a gravitational wave detection system.
Citation Information
Patent Citations
High-purity precious metal evaporation material and preparation method thereof
CN105506557A
Preparation method of Pt-Au alloy
CN110387483A
Gold-platinum alloy quality inspection material for space gravitational wave detection inertial sensor and preparation method of gold-platinum alloy quality inspection material
CN114214538A
Method for densifying and homogenizing gold-platinum alloy material for space gravitational wave detection
CN114410993A